In the middle of conflicts, violence(s), identity (ies) and power relations life inside educational institutions (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
The educational institution as a factor of secondary socialization is currently going through one of the most difficult and complex moments,due, among other reasons, to the growing difficulty in facing the challenges associated with managing the social and cultural conflicts that come together in the classroom;violence as a multifactorial phenomenon, as well as the configuration of identities and power relations, constitute aspects that permeate socio-educational processes,to which the imbalance of the school climate is attributed, for entailing the emergence of confrontations, physical-symbolic territorial struggles, discrimination, subordination and psychological and social impositionsthat exacerbate hostility and deterioration of coexistence. This research as a result of a documentary review, seeks to account for life within educational institutions,specifying as part of the reflection the conflicts, violence(s), identity(ies) and power relations, which manage to reproduce themselves very easily in this scenario due to their difficulty in integrating efforts around the use of mechanismsassociated with the peaceful resolution of daily controversies and the management of intercultural education as an alternative to achieve the consolidation of bonds based on respect for dignity and mutual recognition.It is concluded that life within educational institutions is interwoven by a network of relationships in which both groups and individuals seek to impose cultural and behavioral patterns from the social scene, seeking to gain recognition by appealing to the violence and power.
Keywords: violence(s); power relations; educational institution; identity(ies); social conflicts